Mental Health and HIV Risk in Men Who Have Sex with Men - Safren, Steven A. (2010)
Evidence-based HIV prevention interventions with men who have sex with men (MSM) in the United States have moderate effect sizes in reducing HIV sexual risk behavior. Mental health and psychosocial problems, which both disproportionately affect MSM populations and are implicated in HIV transmission risk behaviors, also likely interfere with the uptake of HIV behavioral interventions. Moreover, given that mental health and psychosocial problems such as depression, substance use, and violence frequently co-occur for many MSM (eg, as “syndemic conditions”), what is probably needed are combination prevention efforts, or prevention “cocktails,” similar to treatment “cocktails,” that address the psychological and behavioral mechanisms that interact to produce elevated risk for HIV. Such interventions should incorporate a holistic framework to address the sexual health and overall well-being of MSM. Addressing co-occurring psychosocial risk factors is apt to improve effect sizes of current HIV prevention interventions and allow for more effective uptake by MSM.